Experimental Study on a Flue Gas Waste Heat Cascade Recovery System under Variable Working Conditions - Jiayou Liu (Energies, 2020)
Recovering flue gas waste heat is beneficial to improving the unit efficiency in power plants. To obtain the change rules of performance parameters of a flue gas waste heat cascade recovery system (FWCRS) under variable working conditions, an experiment bench was designed and built. The variation laws of the inlet temperature and exhaust flue gas temperature of a low temperature economizer (LTE), the inlet and outlet air temperature of an air preheater (AP), the heat exchange quantities of the AP, LTE, and front-located air heater and an additional economizer (AE), as well as the waste heat recovery efficiency, the system exergy efficiency, and the energy grade replacement coefficient were obtained as the flue gas flow, flue gas temperature, bypass flue gas ratio, air temperature, and circulating water flow in AE changed. Using an orthogonal test, the flue gas temperature, bypass flue gas ratio and air temperature were proved to be the significant factors affecting the performance parameters of FWCRS, and the bypass flue gas ratio was suggested as an adjusting parameter of FWCRS under variable working conditions.